A new species of Callistosporium (Callistosporiaceae, Agaricales) from Southwestern China - Feng, Yunli; Shang, Lue; Fang, Yuan; Guo, Xiang; Zhang, Junbo; Yang, Zhenfu; Li, Jianying; Ma, Ming; Hua, Rong; Sun, Dafeng (Phytotaxa, 2026)
Callistosporium jianchuanense sp. nov., collected in Yunnan Province, Dali Bai Autonomous Prefecture, Jianchuan County, Laojunshan Mountain, is proposed based on phylogenetic analyses using ITS and nrLSU and morphological evidence. This new species is characterized by its small-sized basidiomata, an olive grey to olive green pileus covered with grey to black squamules, margins with partial veil remnants, non-striate, hygrophanous lamellae that turn black upon injury. A description, line drawings of microstructures, color images of basidiomata, and phylogenetic analysis results of the new species are provided, along with comparisons with similar species.